2000
DOI: 10.1590/s0036-46652000000300007
|View full text |Cite
|
Sign up to set email alerts
|

A clinical, epidemological, laboratorial, histological and ultrasonographical evaluation of anti-HCV EIA-2 positive blood donors

Abstract: SUMMARYBetween 1992 and 1997, 790 blood donors with anti-HCV EIA-2 strongly reagent (relationship between the sample optical density/cut-off > 3) detected at the blood bank serological screening, were evaluated in ambulatory environment. They were all negative for Chagas disease, syphilis, hepatitis B (HBsAg) and AIDS. Blood samples were collected at the first ambulatorial evaluation, for hemogram, biochemical tests and new serological tests for HCV (anti-HCV EIA-2). In blood samples of 226 repeatedly reagent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…Furthermore, exposure to the virus is higher, due to ignorance about its contamination routes and risk factors, which is consistent with data about C virus world prevalence, that compare population purchasing power (22, 25,35,36). GI individuals lived in smaller cities, compared to controls, who came from larger cities with better health services.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, exposure to the virus is higher, due to ignorance about its contamination routes and risk factors, which is consistent with data about C virus world prevalence, that compare population purchasing power (22, 25,35,36). GI individuals lived in smaller cities, compared to controls, who came from larger cities with better health services.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies relating severe steatosis and cirrhosis due to excessive tobacco use, reported that individuals infected by hepatitis C virus present higher prevalence of these diseases than nontobacco users (11,25,38). Pessione et al (11) observed that cigarette smokers, mostly young ones, had presented a significant augmentantion in damaged liver functions caused by chronic hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence is lower in populations highly selected by previous screening for risk factors associated with the infection, such as blood donors, and is higher among groups highly exposed to parenteral transmission of the virus, such as intravenous drug users or hemodialysis patients 2,13,21,29 . In Brazil, available data usually refer to large centers 8,12,22 . In Londrina, Paraná, data are also very scarce.…”
mentioning
confidence: 99%